Co-management strategies in coastal resource management councils (CRMCs) in Western Visayas - Napilan, Liberty F. (Danyag :the UPV journal of humanities and social sciences, 2003)
"The passage of the Local Government Code (RA 7160) provided for the optimal institutional setting of fisheries co-management in the country. The emergent approach of co-management especially in bay-wide areas is multi-sectoral in nature with iter-LGU partnerships and different resource-sharing schemes. This is based on the premise that complex problems in coastal areas do not respect jurisdictional boundaries and can only be addressed in a meaningful way through collaboration with the different sectors involved. Five coastal resource management councils (CRMCs) in Western Visayas were included in the study: Banate Bay Resource Management Council, Inc. (BBRMCI); Libertad, Pandan, Sebaste, Culasi Baywide Management Council (LIPASECU); Kabankalan, Himamaylan, Ilog Integrated Coastal Area Management Council, Inc. (KAHIL-ICAMCI); Northern Negros Aquatic Resources Management Advisory Council (NNARMAC); and Pilar Bay Management Council (PBMCI). CRMCs were evaluated using the modified key condition matrix of Pomeroy (1992). These are conditions that appear to be central to the chances of developing and sustaining successful co-management arrangements. Roles and power-sharing scheme of the different sectors involved in the said institutional arrangement were also assessed. Success stories or "best practice" strategy were highlighted for possible replication in other coastal communities."